Health and Clinical Management – From the Pen and Paper to the Digital Era - Kubias, D.; Section Editor for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2011)
To present some of the recent best papers in the field of health and clinical management.Synopsis of the best articles selected for the IMIA Yearbook 2011.Of the five selected articles, some confirm the benefits of processing standardized data, others demonstrate the value of adapting the healthcare environment with new technological devices to improve patient safety and healthcare professionals time-efficiency. Other fields are also embraced: the possibilities offered by today’s communication technology open doors largely for telemedicine and remote patient monitoring.In constant evolution, the healthcare environment has multiple challenges to meet: cost containment, increase and ageing of the population, enormous quantities of data and quickly evloving knowledge, complex and multi-disciplinary approaches for healthcare, need for safer care, to mention but a few. While health IT has already helped healthcare in facing these challenges, there still is much more that could be done.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; health and clinical management; patient safety; telemedicine; technology in healthcare